Precalculus (6th Edition)

Published by Pearson
ISBN 10: 013421742X
ISBN 13: 978-0-13421-742-0

Chapter 1 - Equations and Inequalities - Summary Exercises on Solving Equations - Exercises: 16

Answer

$\color{blue}{\left\{\dfrac{1}{3}- \dfrac{i\sqrt2}{3}, \dfrac{1}{3}+ \dfrac{i\sqrt2}{3}\right\}}$

Work Step by Step

Add $1$ to both sides of the equation: $$3x^2-2x+1=-1+1 \\3x^2-2x+1=0$$ The quadratic equation above has $a=3$, $b=-2$, and $c=1$. Solve the equation using the quadratic formula to obtain: $$x=\dfrac{-b \pm \sqrt{b^2-4ac}}{2a} \\x=\dfrac{-(-2) \pm \sqrt{(-2)^2-4(3)(1)}}{2(3)} \\x=\dfrac{2\pm\sqrt{4-12}}{6} \\x=\dfrac{2\pm\sqrt{-8}}{6} \\x=\dfrac{2\pm\sqrt{4(-1)(2)}}{6} \\x=\dfrac{2\pm 2i\sqrt{2}}{6} \\x=\dfrac{2}{6}\pm \dfrac{2i\sqrt2}{6} \\x=\dfrac{1}{3}\pm \dfrac{i\sqrt2}{3}$$ Thus, the solution set is $\color{blue}{\left\{\dfrac{1}{3}- \dfrac{i\sqrt2}{3}, \dfrac{1}{3}+ \dfrac{i\sqrt2}{3}\right\}}$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.